Effect of 2, 5-dimethylphenol on Ca2+ movement and viability in PC3 human prostate cancer cells. (12th June 2016) - Wang, Jue-Long; Chou, Chiang-Ting; Liang, Wei-Zhe; Yeh, Jeng-Hsien; Kuo, Chun-Chi; Lee, Chao-Ying; Shieh, Pochuen; Kuo, Daih-Huang; Chen, Fu-An; Jan, Chung-Ren
Abstract: The phenolic compound 2, 5-dimethylphenol is a natural product. 2, 5-Dimethylphenol has been shown to affect rat hepatic and pulmonary microsomal metabolism. However, the effect of 2, 5-dimethylphenol on Ca 2+  signaling and cyotoxicity has never been explored in any culture cells. This study explored the effect of 2, 5-dimethylphenol on cytosolic free Ca 2+  levels ([Ca 2+ ]i ) and cell viability in PC3 human prostate cancer cells. 2, 5-Dimethylphenol at concentrations between 500 μM and 1000 μM evoked [Ca 2+ ]i rises in a concentration-dependent manner. This Ca 2+  signal was inhibited by approximately half by the removal of extracellular Ca 2+ . 2, 5-Dimethylphenol-induced Ca 2+  influx was confirmed by Mn 2+ -induced quench of fura-2 fluorescence. Pretreatment with the protein kinase C (PKC) inhibitor GF109203X, nifedipine or the store-operated Ca 2+  entry inhibitors (econazole or SKF96365) inhibited 2, 5-dimethylphenol-induced Ca 2+  signal in Ca 2+ -containing medium by ∼30%. Treatment with the endoplasmic reticulum Ca 2+  pump inhibitor thapsigargin in Ca 2+ -free medium abolished 2, 5-dimethylphenol-induced [Ca 2+ ]i rises. Conversely, treatment with 2, 5-dimethylphenol abolished thapsigargin-induced [Ca 2+ ]i rises. Inhibition of phospholipase C (PLC) with U73122 reduced 2, 5-dimethylphenol-evoked [Ca 2+ ]i rises by ∼80%. 2, 5-Dimethylphenol killed cells at concentrations of 350–1000 μM in a concentration-dependent fashion. Chelation of cytosolic Ca 2+  with 1, 2-bis(2-aminophenoxy)ethane- N, N, N ′, N ′-tetraacetic acid/AM (BAPTA/AM) did not prevent 2, 5-dimethylphenol's cytotoxicity. Together, in PC3 cells, 2, 5-dimethylphenol induced [Ca 2+ ]i rises that involved Ca 2+  entry through PKC-regulated store-operated Ca 2+  channels and PLC-dependent Ca 2+  release from the endoplasmic reticulum. 2, 5-Dimethylphenol induced cytotoxicity in a Ca 2+ -independent manner.